2008
DOI: 10.2319/021507-73.1
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Asymmetry in Class II Subdivision Malocclusion

Abstract: Objective: To evaluate the condylar and ramal mandibular asymmetry in a group of patients with Class II subdivision malocclusion to identify possible gender differences between male and female subjects. Materials and Methods: Mandibular asymmetry measurements (condylar, ramal, and condylarplus-ramal asymmetry values) were performed on the panoramic radiographs of 80 subjects (34 male and 46 female). The study group consisted of 40 Class II subdivision patients (18 male and 22 female; mean age 14.53 Ϯ 3.14 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
48
4
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 25 publications
5
48
4
8
Order By: Relevance
“…It has also been used for the assessment of side-to-side dimensional differences and to define the asymmetries (Habets et al 1987, Miller et al 1996, Miller et al 1997, Saglam 2003, Kiki et al 2007, Sezgin et al 2007, Kurt et al 2008. The use of OPG for specific measurements and the determination of differences is controversial owing to considerations relating to magnification and distortion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has also been used for the assessment of side-to-side dimensional differences and to define the asymmetries (Habets et al 1987, Miller et al 1996, Miller et al 1997, Saglam 2003, Kiki et al 2007, Sezgin et al 2007, Kurt et al 2008. The use of OPG for specific measurements and the determination of differences is controversial owing to considerations relating to magnification and distortion.…”
Section: Discussionmentioning
confidence: 99%
“…Kurt et al (2008) investigated condylar and ramal asymmetry in Class II subdivision subjects, and found no significant gender differences when comparing sides. Sezgin et al (2007) found no gender differences in mandibular asymmetry when investigating different occlusion patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations